TRANSLATING IDIOMS AND PROVERBS ACROSS CULTURES - Niyadullayeva Sabrina Shavkat qizi (World Scientific Research Journal, 2025)
Annotation This article explores the linguistic and cultural challenges of translating idioms and proverbs from one language to another. As fixed expressions deeply rooted in national mentality, idioms and proverbs often carry metaphorical meanings that do not have direct equivalents in the target language. The paper analyzes various translation strategies such as literal translation, equivalence, adaptation, and omission, evaluating their effectiveness through real examples in English, Russian, and Uzbek. Special attention is given to the role of cultural context and background knowledge in achieving accurate and culturally appropriate translation. The article concludes that successful translation of idioms and proverbs requires not only linguistic competence, but also a deep understanding of both source and target cultures.